Factors affecting the Gross Domestic Product in Southeast Asia countries / Norhayu Sapri - Sapri, Norhayu (Faculty of Business and Management, 2015)
This study examines the factors affecting the economic growth. Economic grow this the expansion in a nation’s economy which can be deliberate by using several approaches which the most often used is Gross Domestic Product (GDP). Economic growth refers to the quantitative dimension in national income, output per capita or real total output over time in which national income is best approximated by GDP and per capita income. GDP is important to estimate the economic performance of the countries. Thus, in order to increase the GDP we must know the factors that affect it. This study is done to examine the factors that affecting the economic growth which is Gross Domestic Product (GDP) in a few Southeast Asia countries. The factors understudies are macroeconomics variables and demographic variable which are inflation rate, unemployment rate and numbers of population. This research is conduct because researcher wants to analyse the factors affecting economic growth which are in terms of GDP. Many factors were involved in this study which is knowledge about inflation rate, unemployment rate and number of populations in the selected Southeast Asia countries. In this study, the researcher investigates the factors that affecting GDP using panel data from 1999 to 2013 for the five Southeast Asia countries that are Malaysia, Indonesia, Singapore, Thailand and Hong Kong. The researcher wants to estimate whether inflation rate, unemployment rate and number of populations have relationship with the GDP per capita of the Southeast Asia countries. The researcher finds that inflation, unemployment rate and population have relationship with GDP. The researcher has use secondary data in this study. To analyse data and get a best result, researcher use EViews version 7 in order to get descriptive, normality and regression. Lastly the researcher also come out with the conclusion and recommendation about the research that can be done in future.